Pengaruh Gaya Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Di PT. Cemindo Gemilang (Cilegon–Banten) - Zaenal Arifin; Wawan Prahiawan; Ranthy Pancasasti (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2020)
This study aims to examine the effect of Transformational Leadership Style and Organizational Culture on Employee Performance with Job Satisfaction as an Intervening Variable. This study uses quantitative and descriptive approaches, with a approach to causality. The object of this research is PT. Cemindo Gemilang Cilegon - Banten, using a sample of 100 respondents. Questionnaire answers are measured on an interval scale of 1-10. Data were analyzed using the help of SmartPLS Software version 3.0. The results of this study state that: 1) Transformational Leadership Style does not significantly influence employee performance. 2) Organizational culture has a significant effect on employee performance. 3) Transformational leadership has a significant effect on job satisfaction. 4) Organizational culture has a significant effect on job satisfaction. 5) Job satisfaction has a significant effect on employee performance. Job satisfaction fully mediates between transformational leadership and employee performance, while job satisfaction can mediate partially between organizational culture and employee performance.